Exploring Physics Concepts in Lamongan’s Silir-Silir Dance as Innovation in Physics Learning Through an Ethnophysics Approach - Ananda Dwi Pratiwi; Heny Aryani; Salsa Ayu Fajriyah; Suliyanah Suliyanah; Khaled Issa Khalifa Alemgadmi; Utama Alan Deta (Reog: Journal of Ecoethnoscience Education, 2026)
Traditional dance is a form of local wisdom that has great potential to be utilized in the development of contextual physics learning. Silir-Silir dance is a dance typical of Lamongan, East Java, inspired by the wind, the rhythm of nature, and the dynamics of body movement, presenting movement patterns that can be analyzed using the principles of physics. This study aims to identify the physics concepts contained in the Silir-Silir dance, explore how the dance can be used as a learning resource that connects scientific theory with cultural phenomena, and assess its contribution to achieving the Sustainable Development Goals (SDGs) in quality and inclusive education. The research uses a descriptive approach, with data obtained through literature studies, observation of performances and rehearsals, and in-depth interviews with trainers and dancers. The results of the analysis show that the variations in hand movements, changes in tempo, body position shifts, and balance patterns in the dance can be related to the concepts of force, momentum, acceleration, and center of mass. The physical interpretation of these movements shows that Silir-Silir Dance is not only aesthetically valuable but also contains movement structures that can be used as a medium to explain scientific phenomena while reflecting local wisdom, such as harmony with nature, simplicity of life, and the daily traditions of the Lamongan community. Thus, this study shows that the integration of Silir-Silir Dance in culture-based physics learning can strengthen ethnoscience learning, facilitate the understanding of scientific concepts, and foster students' appreciation of local cultural heritage in a contextual and meaningful way.